2022
DOI: 10.1097/md.0000000000029543
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous radiofrequency trigeminal rhizotomy benefits in patients with refractory trigeminal neuralgia

Abstract: A significant number of patients suffers from refractory trigeminal neuralgia (TN) after receiving microvascular decompression (MVD) or other neuro-destructive procedure such as gamma knife radiosurgery (GKRS). This study aims to demonstrate a remediable, reproducible approach to treating refractory pain effectively by percutaneous radiofrequency trigeminal rhizotomy (RF-TR).A total of 392 patients with TN were treated by RF-TR during the past 10 years. Among these patients, 48 cases who had received either MV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
(132 reference statements)
0
1
0
Order By: Relevance
“…A previous study showed that when the NRS score iss >4, the quality of life, sleep and diet are affected. In such cases, the standard clinical diagnosis and treatment protocols typically involve the use of medications or surgical interventions ( 29 ). Based on this, the present study divided patients into NRS0-3 and NRS4-10 categories.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that when the NRS score iss >4, the quality of life, sleep and diet are affected. In such cases, the standard clinical diagnosis and treatment protocols typically involve the use of medications or surgical interventions ( 29 ). Based on this, the present study divided patients into NRS0-3 and NRS4-10 categories.…”
Section: Discussionmentioning
confidence: 99%